Short Communication: Morphological study of the scales of Barbodes cf. binotatus (Cyprinidae) from Toba Lake, Indonesia by using Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS) - khairiza lubis; MUFTI SUDIBYO; ELIDA HAFNI SIREGAR; NURLAINI LAILI (Society for Indonesian Biodiversity, 2021)
Abstract. Lubis K, Sudibyo M, Siregar EH, Laili N. 2021. Short Communication: Morphological study of the scales of Barbodes cf. binotatus (Cyprinidae) from Toba Lake, Indonesia by using Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS). Biodiversitas 22: 3821-3828. Spotted barb (Barbodes cf binotatus) is a freshwater fish of Sumatra Island, especially found in the Toba. The study of morphological characteristics of the scales of Spotted barb (B. cf binotatus) is necessary in fish taxonomy. Therefore, the present study investigated the morphology and the chemical elements of the scales located between the dorsal fin and lateral line and those on the lateral line using SEM-EDS (Scanning Electron Microscope (SEM)- Energy Dispersive X-ray Spectroscopy (EDS). We found that the scales of Spotted barb (B. cf binotatus) have the general morphological characteristics of cycloid scales. The morphologies of the scales between the dorsal fin and lateral line and those on the lateral line are slightly different. Lateral line scales of Spotted barb (B. cf binotatus) have no focus area, replaced by a lateral line canal located along the anterior-posterior axis of the scales with two openings. The anterior opening is bigger and wider in compared to the posterior opening. The circuli of the dorsal fin scale is orientated towards the focus. However, the circuli of the lateral scale faces the lateral line canal. The scales contain some elements such as Ca, K, O, Mg, Na, and P.